Why teachers use Bahasa in the Arabic language classroom? - Mohamed Adnan, Mohamad Azrien; Mohamad, Shukeri; Mamat , Arifin (IIUM Press, 2014)
The use of the target language has long been considered an important principle of second language (L2) instruction. Previous research has attempted to quantify the amount of the first language (L1) used in the classroom and has explored the purposes or functions of teachers’ ‘lapses’ into their students’ L1. The purpose of this qualitative study is to explore the attitudes towards using L1 in Arabic classes among teachers of secondary school in Malaysia which consists of students speaking Bahasa as their L1. Data was collected based on the interviews of the teachers that teach Arabic language in a school. The respondents of this study were two experienced teachers. The findings indicated that L1is still used by the teachers to explain difficult concepts of grammar so that students easily understand linguistics terms, and also to translate new words to ensure that students understand unfamiliar words.